Transparansi Pelayanan Publik di Kantor Kecamatan Kota Timur Kota Gorontalo - David Radjak; Rustam Tohopi; Yakob Noho Nani (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to determine and describe the transparency of service procedures, the ease of procedures, and the ease of obtaining information at the Kota Timur District Office in Gorontalo City. Using a qualitative, descriptive approach through observation, interviews, and documentation, the study results indicate that transparency of service procedures has been effectively implemented through the provision of clear, complete, and easily accessible information to the public. Information regarding service types, requirements, completion times, and fees is published through bulletin boards, brochures, social media, and direct explanations from officers, so that the public can understand the service process without confusion. In terms of ease of procedures, the service flow has been designed to be simple, concise, and user-friendly, ensuring ease of access for service applicants and even for vulnerable groups such as the elderly. Furthermore, the ease of access to information is also evident in the use of various communication channels, both in person and digitally. Information boards, leaflets, social media, and digital displays are actively used to disseminate information so that the public can understand procedures before visiting the office and better prepare documents. Overall, these three indicators demonstrate that the Kota Timur District Office is committed to implementing the principle of transparency in public services, although further innovation is needed to ensure information reaches a wider and more equitable public.